2013
DOI: 10.1037/a0031963
|View full text |Cite
|
Sign up to set email alerts
|

Language ability predicts the development of behavior problems in children.

Abstract: Prior studies have suggested, but not fully established, that language ability is important for regulating attention and behavior. Language ability may have implications for understanding attention-deficit hyperactivity disorder (ADHD) and conduct disorders, as well as subclinical problems. This article reports findings from two longitudinal studies to test (a) whether language ability has an independent effect on behavior problems, and (b) the direction of effect between language ability and behavior problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
165
4
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(193 citation statements)
references
References 85 publications
18
165
4
6
Order By: Relevance
“…Although the diagnostic criterion for SLI excludes psychiatric disorders, there is a consistent association between language impairment and behavioral problems (St Clair et al 2011;Van Agt et al 2011;van Daal et al 2007;Yew and O'Kearney 2013;Gregl et al 2014;Mok et al 2014;Hollo et al 2014;Helland et al 2014). The causal path of this relation remains unclear, but evidence from longitudinal studies suggests the direction of effect may be from language to behavior (Petersen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although the diagnostic criterion for SLI excludes psychiatric disorders, there is a consistent association between language impairment and behavioral problems (St Clair et al 2011;Van Agt et al 2011;van Daal et al 2007;Yew and O'Kearney 2013;Gregl et al 2014;Mok et al 2014;Hollo et al 2014;Helland et al 2014). The causal path of this relation remains unclear, but evidence from longitudinal studies suggests the direction of effect may be from language to behavior (Petersen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is hard for someone to focus his attention on information he cannot fully comprehend. Or attention problems can co-occur with language deficits (Petersen et al, 2013). Petersen et al (2013) state that one possible mechanism linking language to attention and behavior problems would be the use of language in the form of private (self-directed) speech as a regulator.…”
Section: Resultsmentioning
confidence: 99%
“…Language is important for regulating attention and behavior. Language and communication skills can also interfere with socialization (Petersen et al, 2013). When children can communicate their needs they can use more reasoning in negotiating with adults and their peers, preventing them to develop problem behavior.…”
Section: Introductionmentioning
confidence: 99%
“…However, a pair of such studies was reported by Petersen et al. (2013). They modelled the cross‐lagged relationships between behaviour problems and language ability in a sample of 585 children followed between the ages of 7 and 13 years.…”
Section: Introductionmentioning
confidence: 99%
“…(2011), we expected that a longitudinal analysis would show that the language and reading measures would be predictive of later EBD. We expected that EBD would not be a predictor of later language (Petersen et al., 2013) but that it may predict later reading (Trzesniewski et al., 2006). …”
Section: Introductionmentioning
confidence: 99%